Application of Measured Fishing Method in Kei Islands, Maluku Province - Ngabalin, Anna M. (Jurnal Ilmiah Manajemen Kesatuan, 2024)
As an implementation of Government Regulation of the Republic of Indonesia Number 11 of 2023 concerning Measured Fishing in Indonesian waters, the Ministry of Marine Affairs and Fisheries is implementing a priority program agenda by implementing the measured fishing method (Penangkapan Ikan Terukur/PIT) in a number of waters in Indonesia in zone classification. Measured Fishing is a controlled and proportional fishing practice, carried out in special zones with certain quotas to maintain the sustainability of fish resources and their ecosystems. The implementation of this PIT method has been carried out in the province of Maluku, Kei Islands which are included in zone 3. This policy is a response to the serious challenges faced in marine fisheries management, including overfishing and ecosystem degradation. With clear regulations, it is hoped that it can reduce pressure on fish populations and support sustainable economic growth for coastal communities. The implementation of this policy requires support and collaboration between the government, fisheries business actors, academics, and the community to ensure its success. Evaluation and scientific research will be key in measuring the impact and effectiveness of this policy, as well as in identifying areas of improvement needed to improve the sustainability of the fisheries sector in Indonesia for a better future.